Researches for capitalization at a higher quality of the whey - Zmievskiy, Yuriy; Mnerie, Alin; Mnerie, Dumitru; Totorean, Alin (My University, 2014)
In the processing of the milk, the whey is considered in many cases as a product without important value. In recent years it can see the increasingly of the possibilities of superior utilization of the whey. It is recognized for the health benefits of the whey with the both ways for people like prophylactic and also as treatment in the various diseases, including cancer. For greater of the whey value, it can be processed by different technologies in relation with the destination. The paper contains a synthetic overview of the possibilities of recovery of the whey, detailing the use of membrane distillation method for the separation and concentration of whey. For investigation it was applied the method using Russian film composite membranes of the type MFFK-3. For that it has been a study about some influences of natural convention on the specific productivity of the used membranes. The scope of the experiments is the preparation of the membrane distillation (MD) technology for to apply on industry scale for a increasing of the performances of the whey utilizations.
Keywords: whey; membrane distillation; молочна сироватка; мембранна дистиляція; молочная сыворотка; мембранная дистилляция; кафедра технологічного обладнання та комп’ютерних технологій проектування